Symbol

# Calculator search results

Formula
Solve the equation
Graph
$y = 5 \left ( - 1 + 2 x \right ) + 3 \left ( 4 - x \right )$
$y = 0$
$x$Intercept
$\left ( - 1 , 0 \right )$
$y$Intercept
$\left ( 0 , 7 \right )$
$5 \left( -1+2x \right) +3 \left( 4-x \right) = 0$
$x = - 1$
 Solve a solution to $x$
$\color{#FF6800}{ 5 } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 1 } \color{#FF6800}{ + } \color{#FF6800}{ 2 } \color{#FF6800}{ x } \right ) + 3 \left ( 4 - x \right ) = 0$
 Multiply each term in parentheses by $5$
$\color{#FF6800}{ - } \color{#FF6800}{ 5 } + \color{#FF6800}{ 5 } \color{#FF6800}{ \times } \color{#FF6800}{ 2 } \color{#FF6800}{ x } + 3 \left ( 4 - x \right ) = 0$
$- 5 + 5 \times 2 x + \color{#FF6800}{ 3 } \left ( \color{#FF6800}{ 4 } \color{#FF6800}{ - } \color{#FF6800}{ x } \right ) = 0$
 Multiply each term in parentheses by $3$
$- 5 + 5 \times 2 x + \color{#FF6800}{ 3 } \color{#FF6800}{ \times } \color{#FF6800}{ 4 } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } = 0$
$- 5 + \color{#FF6800}{ 5 } \color{#FF6800}{ \times } \color{#FF6800}{ 2 } \color{#FF6800}{ x } + 3 \times 4 - 3 x = 0$
 Simplify the expression 
$- 5 + \color{#FF6800}{ 10 } \color{#FF6800}{ x } + 3 \times 4 - 3 x = 0$
$- 5 + 10 x + \color{#FF6800}{ 3 } \color{#FF6800}{ \times } \color{#FF6800}{ 4 } - 3 x = 0$
 Multiply $3$ and $4$
$- 5 + 10 x + \color{#FF6800}{ 12 } - 3 x = 0$
$\color{#FF6800}{ - } \color{#FF6800}{ 5 } + 10 x \color{#FF6800}{ + } \color{#FF6800}{ 12 } - 3 x = 0$
 Add $- 5$ and $12$
$\color{#FF6800}{ 7 } + 10 x - 3 x = 0$
$7 + \color{#FF6800}{ 10 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } = 0$
 Calculate between similar terms 
$7 + \color{#FF6800}{ 7 } \color{#FF6800}{ x } = 0$
$\color{#FF6800}{ 7 } \color{#FF6800}{ + } \color{#FF6800}{ 7 } \color{#FF6800}{ x } = 0$
 Organize the expression 
$\color{#FF6800}{ 7 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 7 } = 0$
$7 x \color{#FF6800}{ + } \color{#FF6800}{ 7 } = 0$
 Move the constant to the right side and change the sign 
$7 x = \color{#FF6800}{ - } \color{#FF6800}{ 7 }$
$\color{#FF6800}{ 7 } \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 7 }$
 Divide both sides by the same number 
$\color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 1 }$
Have you found the solution you wanted?
Try again
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture